Measurement of carbon dioxide production in very low birth weight babies. Issue 1 (1st July 2000) - Kingdon, C C; Mitchell, F; Bodamer, O A F; Williams, A F
Abstract : BACKGROUND: CO2 production is most commonly measured by using indirect calorimetry to quantify elimination of CO2 in breath (Vco 2 ). An alternative is to measure the rate at which CO2 appears in the body pool (Raco 2 ) by infusing a 13 C labelled bicarbonate tracer. Vco 2 and Raco 2 generally differ but are related by c, a factor that adjusts for the incomplete recovery of infused tracer in the breath. The literature relating to human studies cites a wide range of values for c but the only neonatal study to determine c empirically estimated a mean value of 0.77. AIM: To estimate fractional recovery rate, c, in very low birthweight babies, and assess the feasibility of using the isotopic technique to measure CO2 production during mechanical ventilation. METHOD: Eleven spontaneously breathing, continuously fed, very low birthweight infants (median birth weight 1060 g, median gestational age 29 weeks) were studied. RESULTS: Mean (SD) Vco 2 was 9.0 (2.0) ml/min (standard temperature and pressure dry, STPD) and mean (SD) Raco 2 was 9.6 (2.1) ml/min (STPD). The mean (SD) value of c was estimated as 0.95 (0.13). The 95% confidence intervals of the mean were 0.87–1.03. CONCLUSIONS: The results emphasise the importance of measuring c for a given study population rather than assuming a value based on adult studies. The close approximation of Raco 2 and Vco 2 in this group of babies implies that the labelled bicarbonate infusion technique could be used to measure simply CO2 production during mechanical ventilation.